The objective assessment of personality. An alternative to self-report based assessment - José Santacreu; Victor J. Rubio; José Manuel Hernández (Análisis y Modificación de Conducta, 2025)
The objective of this papel is to present an alternative to traditional personality measures based on Cattell´s T-data.